ղ . IJ.

  1. III
  2. 4.
  3. II. ղ.
  4. 2. . .
  5. 7. .

u = f (x, y, z). (, yo, zo) 3- . , . (sa, cosb, cosg) . . , M. . l- , (Lcosa, lcosb, lcosg)C :

(X-xo, y-yo, z-zo). . :

(2) (1)

u = f (Xo + lcosa, Yo + lcosb, Zo + lcosg). . u- .

: l, l = 0 u = f (x, y, z) , l. :

: 䳺 u = f (x, y, z) (xo, yo, zo) , grad (Mo) =

: u = f (x1, x2, ..., xn) Mo (

䳺:

1. 䳺 y = f (x, y, z) .

2. u = f (x, y, z) , 䳺 -

䳺:

: ˳ u = f (x, y) .

M (X, Y) , -䳺 .

- u = f (x, y, z) (xo, yo, zo) .

: Mo (xo, yo, zo) , 䳺 .



ֲ ί ֲ. | Ͳ ղͲ ʲ ֲ N ̲.

. | ² ֲ. | . | N | ֲ N ̲. ֲ N ̲. | Ͳ ֲ N ̲. | Ͳ ί ֲ. | Ͳ ղͲ ֲ N ̲. | N ̲. | ֲ ֲ N ̲. |

© um.co.ua -